2023
DOI: 10.3390/vaccines11050942
|View full text |Cite
|
Sign up to set email alerts
|

BBIBP-CorV Vaccination against the SARS-CoV-2 Virus Affects the Gut Microbiome

Abstract: Several observational studies have confirmed that the severe acute respiratory syndrome coronavirus2 (SARS-CoV-2) might substantially affect the gastrointestinal (GI) system by replicating in human small intestine enterocytes. Yet, so far, no study has reported the effects of inactivated SARS-CoV-2 virus vaccines on gut microbiota alterations. In this study, we examined the effects of the BBIBP-CorV vaccine (ChiCTR2000032459, sponsored by the Beijing Institute of Biological Products/Sinopharm), on gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…However, several studies reported unaltered or diminished microbial diversity after vaccination, which is contradictory to our results ( Eloe-Fadrosh et al., 2013 ; Hagan et al., 2019 ; Tang et al., 2022 ). Herein, elevated microbial diversity may potentially be due to the increase in the population of rare taxa which are not typically abundant in the absence of an immune stimuli, as observed elsewhere ( Seekatz et al., 2013 ; Shen et al., 2023 ). IFN-elevated secretory IgA and systemic IgG could also increase the microbial diversity of the gut ( Zeng et al., 2016 ; Yang and Palm, 2020 ; Ishizaka et al., 2023 ), consistent with our results.…”
Section: Discussionmentioning
confidence: 94%
“…However, several studies reported unaltered or diminished microbial diversity after vaccination, which is contradictory to our results ( Eloe-Fadrosh et al., 2013 ; Hagan et al., 2019 ; Tang et al., 2022 ). Herein, elevated microbial diversity may potentially be due to the increase in the population of rare taxa which are not typically abundant in the absence of an immune stimuli, as observed elsewhere ( Seekatz et al., 2013 ; Shen et al., 2023 ). IFN-elevated secretory IgA and systemic IgG could also increase the microbial diversity of the gut ( Zeng et al., 2016 ; Yang and Palm, 2020 ; Ishizaka et al., 2023 ), consistent with our results.…”
Section: Discussionmentioning
confidence: 94%
“…These findings suggest that vaccination alters the composition of microbiota and its metabolites in the gut. 129 The gut microbiota is associated with the vaccine response, which provides a basis for further exploring the regulation of the gut microbiota to improve vaccine efficacy. Newborns can obtain immune protection against SARS‐CoV‐2 through antibodies generated by the vaccine in breast milk, and vaccines can induce changes in the composition of the human breast milk microbiome, which may affect the antibody level.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%